El tesoro de Regina Turdulorum (Casas de Reina, Badajoz) - Chico, David Martínez, (Access archaeology., 2021)
The Regina Turdulorum Hoard (Casas de Reina, Badajoz) was buried with 818 imitative antoniniani of Divo Claudio type, minted in copper. The vast majority of the coins bear the reverse legend CONSECRATIO. This figure makes the Regina Turdulorum hoard one of the most important in Spain and Portugal. In numismatic terms, the most common reverse type is the funeral pyre, as opposed to the eagle. In addition to this main group, there is a second group, where there are curious imitations that follow various prototypes for the manufacture of the reverse. The study of the posthumous coinage of Claudius II and his imitations represents one of the most complex tasks in ancient numismatics. The work is considerably complicated by the fact that they are highly copied coins, which means that regular issues are very difficult to distinguish from the imitations.